Photopic and scotopic VEPs in patients with congenital stationary night-blindness - Kubová, Zuzana; Kremlácek, Jan; Kuba, Miroslav; Chlubnová, Jana; Sverák, Jaromir (Documenta ophthalmologica. Advances in ophthalmology, 2004)
Extended set of visual evoked potentials (VEPs) using pattern-reversal (PREPs), linear motion-onset and radial (expansion) motion-onset stimuli (M-VEPs) (detailed specification at http://www.lfhk.cuni.cz/elf) was used to verify congenital stationary night-blindness (CSNB) characteristics in 7 patients (compared to 7 age matched controls) in photopic conditions (luminance of 17 cd/m2). No differences were found in any of the M-VEPs, whilst PREPs displayed prolonged latencies in 3 of 7 CSNB patients. Additionally, the PREPs and M-VEPs were tested in 3 normal and 3 CSNB subjects (the only available ones from the original group) over large range of scotopic, mesopic and photopic luminances (from 0.0001 to 65.4 cd/m2). Both types of low luminance VEPs had distinctly increased luminance threshold needed for reliable VEPs eliciting in CSNB patients (0.06 cd/m2) when compared with controls (0.003 cd/m2); the VEP appearance threshold was almost identical with the perceptual threshold in both groups. Thus, our pilot study proved that CSNB can be objectively detected also via scotopic VEP examination. Since the prolonged PREP latencies at 17 cd/m2 normalised with luminance increase, it indicates that the lower luminance stimuli (compared to the standard recommended by ISCEV) can be more sensitive for some visual disorders detection.
Keywords: Pattern Recognition, Visual; Humans; světlo; tyčinky retiny; Visual Pathways; senzorické prahy; lidé; Night Blindness; mladiství; Light; rozpoznávání obrazu; zrakové evokované potenciály; Sensory Thresholds; Retinal Rod Photoreceptor Cells; noční slepota; Adolescent; adaptace na tmu; zrakové dráhy; Evoked Potentials, Visual; Dark Adaptation